1998
DOI: 10.1523/jneurosci.18-21-08805.1998
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Postsynaptic Density-93 to Dendritic Microtubules and Interaction with Microtubule-Associated Protein 1A

Abstract: Postsynaptic density-93 (PSD-93)/Chapsyn-110 is a member of the membrane-associated guanylate kinase (MAGUK) family of PDZ domain-containing proteins. MAGUKs are widely expressed in the brain and are critical elements of the cytoskeleton and of certain synapses. In the ultrastructural studies that are described here, PSD-93 localizes to both postsynaptic densities and dendritic microtubules of cerebellar Purkinje neurons. The microtubule localization is paralleled by a high-affinity in vivo interaction of PSD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 62 publications
6
144
0
1
Order By: Relevance
“…For example, the GK domain plays an essential role in forming the structural arrangement of SAP97, which is needed for Kir3.2c sensitization to G proteins by SAP97. It was reported that the GK domain bound to SH3 but not any PDZ domains within PSD-95 as well as DLG molecules (Brenman et al, 1998;McGee and Bredt, 1999). This intramolecular interaction between SH3 and GK domains may be a candidate for the mechanism of the structural arrangement of SAP97.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, the GK domain plays an essential role in forming the structural arrangement of SAP97, which is needed for Kir3.2c sensitization to G proteins by SAP97. It was reported that the GK domain bound to SH3 but not any PDZ domains within PSD-95 as well as DLG molecules (Brenman et al, 1998;McGee and Bredt, 1999). This intramolecular interaction between SH3 and GK domains may be a candidate for the mechanism of the structural arrangement of SAP97.…”
Section: Discussionmentioning
confidence: 90%
“…The anchoring proteins also act as scaffolds by arranging signal molecules in a certain order that is determined by the specific binding of signal molecules to different PDZ domains. Recent studies have revealed that the GK domain of PSD/SAP family proteins, although it has no guanylate kinase activity , acts as a binding domain for SAPAPs/GKAP/PAP Satoh et al, 1997;Takeuchi et al, 1997), MAP1A (Brenman et al, 1998), BEGAIN (Deguchi et al, 1998) or the kainate receptor (Garcia et al, 1998). However, the functional role of the GK domain has remained largely unclarified.…”
Section: Discussionmentioning
confidence: 99%
“…Each domain in the SAP subfamily of MAGUKs is highly conserved and has been shown to be a site of protein-protein interaction: PDZ domains bind voltage-and ligand-gated ion channels (3,9); SH3 domains interact with proline-rich, PXXPR-like sequences (3,4,10) as well as with the GK domain of CASK (11); GKAP/SAPAP (12)(13)(14), the microtubule-associated protein MAP1A (15), the brain-enriched guanylate kinase associated protein (BEGAIN) (16), and the guanylate kinase associated kinesin GAKIN (17) are interaction partners of the GK domain. The GK domain is catalytically inactive, although structurally closely related to authentic guanylate kinases as we have shown in previous work (18,19).…”
mentioning
confidence: 99%
“…The GK domain of the PSD-95 family of MAGUKs interacts with the GKAP/SAPAP/DAP family of postsynaptic density proteins Naisbitt et al, 1997;Takeuchi et al, 1997), BEGAIN (Deguchi et al, 1998), and MAP1A (Brenman et al, 1998). GKAP in turn interacts with a novel postsynaptic scaffold protein termed Shank Naisbitt et al, 1999;Tu et al, 1999).…”
mentioning
confidence: 99%